Genome Wide In silico Analysis of the Mismatch Repair Components of Plasmodium falciparum and Their Comparison with Human Host - Tarique, Mohammed; Ahmad, Moaz; Chauhan, Manish; Tuteja, Renu (Frontiers in Microbiology, 2017)
Malaria a major parasitic infection globally particularly in tropical and sub-tropical regions of the world is responsible for about 198 million cases and estimated deaths due to this disease are about 0.6 million. The emergence of drug resistance in the malaria parasite is alarming and it is necessary to understand its underlying cause and molecular mechanisms. It has been established that drug resistant malaria parasites have defective mismatch repair (MMR) therefore it is essential to study this pathway and its components in detail. Recently a number of non-synonymous Single Nucleotide Polymorphisms have been reported in genes involved in MMR pathways. PfMLH is an endonuclease essential to restore the MMR in drug resistant strains of Plasmodium falciparum. Considering all these facts about the role of MMR in emergence of drug resistant parasite, in this manuscript we report a genome wide analysis of the components of the MMR pathways such as MLH, Pms1, MSH2-1, MSH2-2, MSH6 and UvrD using in silico bioinformatics based approaches. The phylogenetic analysis revealed evolutionary closeness with the MMR components of various organisms. It is noteworthy that P. falciparum contains two homologues of MSH2, which are located on different chromosomes. The structural modeling of these components showed their similarity with the human/yeast MMR components. The docking studies reveal that PfUvrD and PfMLH interact with each other. The in-silico identification of interacting partners of the major MMR components identified numerous P. falciparum specific proteins. In line with our previous studies the present study will also contribute significantly to understand the MMR pathway of malaria parasite.